Treatment of Acute Achilles Tendon Rupture - Park, Seung-Hwan; Lee, Ho Seong; Young, Ki Won; Seo, Sang Gyo (Clinics in orthopedic surgery, 2020)
There is no clear consensus on the optimal treatment of acute Achilles tendon rupture. Recently, studies have demonstrated the critical role of functional rehabilitation in the treatment of ruptured Achilles tendons. Hence, conservative treatment is preferred by a growing number of surgeons seeking to treat the condition without the risk of complications from surgery. However, operative treatment is still considered as a more reliable treatment option for acute Achilles tendon rupture. In this review article, we provide an overview of recent treatment strategies for acute rupture of the Achilles tendon.